2012
DOI: 10.1038/cdd.2012.90
|View full text |Cite
|
Sign up to set email alerts
|

TRAIL induces necroptosis involving RIPK1/RIPK3-dependent PARP-1 activation

Abstract: Although TRAIL (tumor necrosis factor (TNF)-related apoptosis inducing ligand) is a well-known apoptosis inducer, we have previously demonstrated that acidic extracellular pH (pHe) switches TRAIL-induced apoptosis to regulated necrosis (or necroptosis) in human HT29 colon and HepG2 liver cancer cells. Here, we investigated the role of RIPK1 (receptor interacting protein kinase 1), RIPK3 and PARP-1 (poly (ADP-ribose) polymerase-1) in TRAIL-induced necroptosis in vitro and in concanavalin A (Con A)-induced murin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
230
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 313 publications
(242 citation statements)
references
References 40 publications
6
230
1
Order By: Relevance
“…49 Primary Ripk3 þ / þ and Ripk3 À / À MEFs were isolated from E12.5 littermate embryos following standard protocol. The Tak1 þ / þ and Tak1 À / À MEFs were kindly provided by Dr. Takeuchi.…”
Section: Cell Lines Sv40 Large T-immortalizedmentioning
confidence: 99%
“…49 Primary Ripk3 þ / þ and Ripk3 À / À MEFs were isolated from E12.5 littermate embryos following standard protocol. The Tak1 þ / þ and Tak1 À / À MEFs were kindly provided by Dr. Takeuchi.…”
Section: Cell Lines Sv40 Large T-immortalizedmentioning
confidence: 99%
“…Necroptosis mediated by TNF was previously described to be independent of and distinct from PARP-1 activation (11). On the contrary, TRAIL was previously described to induce necroptosis dependent on PARP-1 under acidic-pH conditions (31). Three PARP-1 inhibitors, PJ-34, 3-AB, and olaparib, rescued cells from the formation of TRAIL-zVAD-mediated PAR chains in a concentration-dependent manner (Fig.…”
Section: Atg5 But Not Atg16l1 or Receptor Internalization Promotes Trmentioning
confidence: 79%
“…1C), which are known to downregulate the protein level of RIPK1 (30). Furthermore, the main role of RIPK1 during necroptosis was confirmed for all analyzed cell lines (L929Ts, NIH 3T3, Jurkat, and HT-29), as Nec-1s (analogue of Nec-1, a specific and stable RIPK1 inhibitor, but lacking the targeting effect on the immunomodulatory enzyme indoleamine 2,3-dioxygenase [IDO] [31]) prevented the execution of TRAIL-mediated necroptosis (Fig. 1D).…”
Section: Resultsmentioning
confidence: 98%
“…44,45 However, genetic ablation or pharmacological inhibition of RIPK1 failed to block PARP1-mediated cell death induced by DNA alkylating agents. 46 Our data also showed that the kinase activity of RIPK1 did not affect PARP1-dependent necrosis in response to H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%